2017
DOI: 10.3174/ajnr.a5051
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of the Impact of Regional Intracranial Atherosclerotic Lesions on Brain Arterial 3D Hemodynamics

Abstract: Regional intracranial atherosclerotic lesions not only alter distal arterial flow but also significantly affect ipsilateral collateral arterial hemodynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Ruland et al reported possible PCA‐to‐MCA collateral flow pathway in stenotic MCA patients. Wu et al also proposed PCA compensation in addition to increased blood flow in the ipsilateral ACA in patients with MCA stenosis, which was in agreement with findings of Brass et al We observed similar changes in a number of ICAD patients. However, the comparison of FR and PV between ipsilateral and contralateral vessels may be unreliable because of anatomic variations in the CoW .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Ruland et al reported possible PCA‐to‐MCA collateral flow pathway in stenotic MCA patients. Wu et al also proposed PCA compensation in addition to increased blood flow in the ipsilateral ACA in patients with MCA stenosis, which was in agreement with findings of Brass et al We observed similar changes in a number of ICAD patients. However, the comparison of FR and PV between ipsilateral and contralateral vessels may be unreliable because of anatomic variations in the CoW .…”
Section: Discussionsupporting
confidence: 91%
“…For instance, there was an outlier in the moderate subgroup (Figure A, PD of 3.79 mm Hg and hemisphere PV ratio of 2.56), where the blood flow redistibution may be influenced by 2 opposing phenomena. The subject presented with an aplastic A1 segment of the contralateral ACA, a normal CoW anatomic variant, resulting in increased blood flow to ipsilateral ICA and ACA, as opposed to the stenotic MCA effect that is associated with blood flow reduction in ipsilateral ICA . Therefore, in this patient, the FR and PV of ipsilateral ICA increased instead of decreasing.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In a preliminary study, Hope et al (21) suggested time-of-flight MRA to be inferior to 4D flow MRI in the hemodynamic assessment of patients with intracranial atherosclerotic disease. In a separate study, 4D flow MRI characterized asymmetric flow indices in patients with intracranial atherosclerotic disease compared to age-appropriate controls (67), influencing both distal and ipsilateral collateral arterial hemodynamics. Quantitative hemodynamic data using 4D flow MRI may provide additional insight into the pathophysiology and risk stratification of intra-/extra-cranial atherosclerotic disease based on tissue susceptibility to low flow states or poor augmentation of collateral flow.…”
Section: Atherosclerosis (Intra-/extra-cranial Atherosclerotic Disease)mentioning
confidence: 99%